(untitled) (Veterinary Science, 2019)
The objective of the present study was to evaluate some socio-productive aspects of goat producers in the area of Malargüe, Mendoza, including within the strip of owners of between 480-640 animal, sector which accounts for 294 establishments, 23.4% of the total of goat farms in the region. A structured survey was organized for this, where age, formal education, knowledge of technology, importance of marketing, reproduction, animal health, associations, among others were consulted. For the statistical study of the data applied analysis of variance with Tukey tests for media differentiation was used, for the quantitative information and for the study of the qualitative variables a contingency table 2 X, with p≤0 , 05 for the characterization of groups was used. Results showed that 83.3% of producers are over 45 years of age, only 38% has complete primary education, 54.2% admitted knowing the existence of technology to improve their productive system, 77% does not give importance to reproductive management of their herd, only 10.4% believed in the importance of health, while 79% said that the associations would improve their income. In conclusion only one third of the producers has completed the primary cycle of formal education, most of goat producers in this sector have access to and knowledge of technologies, in spite of this, they have low consideration towards the need for applying reproductive management and health rules and a very important percentage considered associations to improve economic income.